Neuropsychological functions of verbal recall and psychomotor speed significantly affect pain tolerance - Jacobsen, Henrik Børsting; Stubhaug, Audun; Schirmer, Henrik; Landrø, Nils Inge; Wilsgaard, Tom; Mathiesen, Ellisiv B.; Nielsen, Christopher Sivert (European Journal of Pain, 2019)
Source at https://doi.org/10.1002/ejp.1437 . Background - Effects from cognitive performance on pain tolerance have been documented, however, sample sizes are small and confounders often overlooked. We aimed to establish that performance on neuropsychological tests was associated with pain tolerance, controlling for salient confounders. Methods - This was a cross‐sectional study nested within the Tromsø‐6 survey. Neuropsychological test performance and the cold pressor test were investigated in 4,623 participants. Due to significant interaction with age, participants were divided into three age groups (<60, ≥60 to <70 and ≥70 years). Cox proportional hazard models assessed the relationship between neuropsychological tests and cold pressure pain tolerance, using hand‐withdrawal as event. The fully adjusted models controlled for sex, education, BMI, smoking status, exercise, systolic blood pressure, sleep problems and mental distress. Results - In the adjusted models, participants aged ≥70 years showed a decreased hazard of hand withdrawal of 18% (HR 0.82, 95% CI (0.73, 0.92) per standard deviation on immediate verbal recall, and a decreased hazard of 23% (HR 0.77, 95% CI (0.65, 0.08) per standard deviation on psychomotor speed. Participants aged ≥60 to <70 years had a significant decreased hazard of 11% (HR 0.89, 95% CI (0.80, 0.98) per standard deviation on immediate word recall. In participants aged <60 years, there was a decreased hazard of 14% (HR 0.86 95% CI: 0.76, 0.98), per standard deviation on psychomotor speed. Conclusion - Better performance on neuropsychological tests increased pain tolerance on the cold pressor test. These exposure effects were present in all age groups. Significance - This paper describes substantial associations between cognitive functioning and cold pressor tolerance in 4,623 participants. Reduced psychomotor speed and poor verbal recall gave greater odds for hand‐withdrawal on the cold pressor task. The associations were stronger in older participants, indicating an ...